Alternative framing techniques - Shopware (Firm).; NAHB Production Group ([United States] : Shopware, 2004)
Alternative framing techniques can reduce structural lumber requirements and costs, as well as offer design improvements, such as openings in steel-frame studs that allow for the running of plumbing or electrical systems. This video looks at some of the more popular industry options in terms of materials and construction plans.
Execitove producer, Chris Scherer.
Keywords: Roofs; House framing; House construction